PENGARUH PENGUKUSAN TERHADAP KUALITAS BIJI TENGKA- WANG (SHOREA STENOPTERA) (effect of steaming on the quality of tengkawang (shorea stenoptera) seed) - Suwardi Sumadiwangsa (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
The experiment is to study the steaming effect of tengkawang seed (Shorea stenoptera) on both yield and quality.The steam period of samples is 0,15,20,25. And 30 minutes at temperature of 97.5°C and at ambient pressure. A sample was extracted by hydraulic prassing at 25 kg/cm2 and temperaturee of 90°C for one hour.The determinations including yield of fat, acid value, peroxid value, saponification value, iodine value. impurity, water content, melting point, and specific gravity.The experiment shows that the more steaming period, the less yield of at. Fat qualities are affected by steaming periods, except Iodine value, Melting point, and lmpurity. However the fat yield and its qulity of the untreated seed is better than the treated ones.